12-Molybdophosphoric acid anchored on aminopropylsilanized magnetic graphene oxide nanosheets (Fe3O4/GrOSi(CH2)3–NH2/H3PMo12O40): a novel magnetically recoverable solid catalyst for H2O2-mediated oxidation of benzylic alcohols under solvent-free conditions. Issue 13 (12th February 2018) - Farhadi, Saeed; Hakimi, Mohammad; Maleki, Mansoureh
Abstract : 12-Molybdophosphoric acid was anchored on magnetic aminopropylsilanized graphene oxide nanosheets and used as a magnetically recoverable catalyst for solvent-free selective oxidation of benzylic alcohols into the carbonyl compounds with H2 O2 . Abstract : In this work, 12-molybdophosphoric acid (H3 PMo12 O40, HPMo) was chemically anchored onto the surface of aminosilanized magnetic graphene oxide (Fe3 O4 /GrOSi(CH2 )3 –NH2 ) and was characterized using different physicochemical techniques, such as powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, energy-dispersive X-ray analysis (EDX), scanning electron microscopy (SEM), BET specific surface area analysis and magnetic measurements. The results demonstrated the successful loading of HPMo (∼31.5 wt%) on the surface of magnetic aminosilanized graphene oxide. XRD patterns, N2 adsorption–desorption isotherms and SEM images confirm the mesostructure of the sample. FT-IR and EDX spectra indicate the presence of the PMo12 O40 3− polyanions in the nanocomposite. The as-prepared Fe3 O4 /GrOSi(CH2 )3 –NH2 /HPMo nanocomposite has a specific surface area of 76.36 m 2 g −1 that is much higher than that of pure HPMo. The selective oxidation of benzyl alcohol to benzaldehyde was initially studied as a benchmark reaction to evaluate the catalytic performance of the Fe3 O4 /GrOSi(CH2 )3 –NH2 /HPMo catalyst. Then, the oxidation of a variety of substituted primary and secondary activated benzylic alcohols was evaluated with H2 O2 under solvent-free conditions. Under the optimized conditions, all alcohols were converted into the corresponding aldehydes and ketones with very high selectivity (≥99%) in moderate to excellent yields (60–96%). The high catalytic performance of the nanocomposite was ascribed to its higher specific surface area and more efficient electron transfer, probably due to the presence of GrO nanosheets. The nanocomposite catalyst is readily recovered from the reaction mixture by a usual magnet and reused at least four times without any observable change in structure and catalytic activity.